ANALISIS BEBAN KERJA PETUGAS ADMISI RAWAT JALAN DENGAN MENGGUNAKAN METODE WORK LOAD INDICATOR STAFF NEED DI RUMAH SAKIT UMUM DAERAH SIDOARJO - Ummu Latifah; Alfina Aisatus Saadah (Jurnal Kesehatan, 2024)
Workload also takes into account the standard number of employees according to the profession, qualification standards and job evaluation standards. So, the high or low workload does not only depend on the number of workers available, but also depends on the qualifications of the health workers. HR planning can be done by carrying out calculations using the Work Load Indicator Staff Need (WISN) method. Based on interviews conducted by researchers with one of the outpatient admissions officers, information was obtained that the number of outpatient clinic patients in March 2023, 749 patients registering for inpatient admissions, sometimes made the outpatient admissions officers overwhelmed during the patient registration process. The number of outpatient admissions officers is only one person and is not comparable to the number of patient visits from outpatient clinics who will be registered for inpatient care. This causes the workload of officers to become excessive and results in fatigue impact on outpatient admissions officers and outpatient admissions services become less effective and efficient. The aim of this research is to analyze the workload of outpatient admissions officers at Sidoarjo Regional Hospital using the Work Load Indicator Staff Need (WISN) method with quantitative descriptive research methods and observation and interview methods. The results show that the number of outpatient admissions officers is 1 person, the available working time is 120,210 minutes per year, the standard workload is 24,785.56 minutes per year, the slack standard is 0.102 minutes per year, the workforce requirement for outpatient admissions officers is 2 people so it is recommended to add 1 person. outpatient admissions officer and a D3 Medical Records graduate.